Photothermal Bacterial Clearance Using Gold Nanoshells Grown on Chitosan Nanoparticles Dielectric Templates - Patricia Dolores Martinez-Flores; Marisol Gastelum-Cabrera; Manuel G. Ballesteros-Monrreal; Pablo Mendez-Pfeiffer; Marco Antonio Lopez-Mata; Gerardo García-González; Gerardo Erbey Rodea-Montealegre; Josué Juárez (Drugs and Drug Candidates)
Background/Objectives: Bacterial infections remain among the top ten major public health concerns, contributing to a high number of incidences of disease and mortality worldwide, exacerbated by the rise of multidrug-resistant bacteria (MDRB). Consequently, it is crucial to develop novel antimicrobial strategies, including the use of functional nanoparticles. Gold nanoparticles (GNPs) have emerged as promising candidates due to their unique optical properties, particularly their ability to efficiently convert absorbed light into heat through the photothermal (PT) effect, which can be harnessed for bacteria eradication. Methods: Chitosan was modified with 3-mercaptopropionic acid to introduce sulfur groups, facilitating gold deposition onto chitosan nanoparticle (TCNPs) surface. The gold shell was subsequently formed via a seed-mediated method, wherein gold seeds were adsorbed onto TCNPs and further grown to form the shell. Photothermal effect on the bacterial viability was evaluated. Results: TCNPs with a size of 178 nm and spherical morphology were obtained. After the gold shell (TCNP@Au) exhibited a photothermal conversion efficiency of 31%, making them a promising photothermal agent for bacterial clearance. Notably, the viability of Escherichia coli was significantly reduced in the presence of TCNP@Au and was almost eradicated upon PT treatment. In contrast, TCNP@Aus were non-toxic for Staphylococcus aureus. Conclusions: TCNP@Au demonstrated favorable photothermal properties, presenting a novel nanoplatform for antibacterial applications, particularly against Gram-negative bacteria. However, further investigation is required to optimize the PT-based strategies against Gram-positive bacteria, such as S. aureus.